Improving the methodology of a systematic approach to analyzing the effectiveness and quality of outsourcing services - Ergasheva Nasiba Rakhmatullaevna (THE INNOVATION ECONOMY, 2026)
This article is based on the analysis of a systematic approach to the analysis of improving the efficiency and quality of outsourcing services, including the goals and objectives of outsourcing services, the choice of the outsourcing services market by the client, the identification of important features and characteristics of preschool educational organizations and their classification, the presentation of outsourcing in preschool educational organizations as a set of processes, and scientifically based proposals and recommendations for the classification of individual processes in this service and their important features